2015
DOI: 10.1017/s0003055415000301
|View full text |Cite
|
Sign up to set email alerts
|

War and Revenge: Explaining Conflict Initiation by Democracies

Abstract: W hile we know much about what differentiates the conflict behavior of democracies from autocracies, we know relatively little about why some democracies are more belligerent than others. In contrast to existing studies, I argue that it is public opinion and not institutions that drives these differences. All democratic leaders have an incentive to take public opinion into account, but public opinion is not the same everywhere. Individuals' attitudes towards war are shaped by core beliefs about revenge, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 117 publications
(179 reference statements)
2
34
0
Order By: Relevance
“…In his landmark study, Pinker (2011) argues that trends in warfare, in murder rates, and even in the physical punishment of children have common root causes. In a similar vein, studies of elites and public opinion have shown that attitudes towards punishment and retribution domestically correlate with support for hawkish policies internationally (Liberman, 2006;Liberman, 2007;Rathbun, 2007;Liberman, 2013;Stein 2015). While most of these studies examine variation within American society, we demonstrate that there are also important variations across liberal democracies.…”
Section: Resultssupporting
confidence: 70%
“…In his landmark study, Pinker (2011) argues that trends in warfare, in murder rates, and even in the physical punishment of children have common root causes. In a similar vein, studies of elites and public opinion have shown that attitudes towards punishment and retribution domestically correlate with support for hawkish policies internationally (Liberman, 2006;Liberman, 2007;Rathbun, 2007;Liberman, 2013;Stein 2015). While most of these studies examine variation within American society, we demonstrate that there are also important variations across liberal democracies.…”
Section: Resultssupporting
confidence: 70%
“…Retributive individuals punish others for not adhering to reciprocity norms. An “eye for an eye” is one of the oldest moral principles on record, and it plays a prominent role in attitudes toward international security (Liberman, ; Stein, ). Moral psychologists distinguish between this desire to punish transgressors for their bad behavior because they deserve it and the authoritarian desire to punish for societal good (Aharoni & Fridlund, ; Carlsmith & Darley, ).…”
Section: Moral Void: the Absence Of Empirical Ethics In The Study Of mentioning
confidence: 99%
“…Previous research has shown that countries with punitive domestic criminal systems are more likely to be confrontationist towards countries breaking international norms (Wagner ; Wagner & Onderco ), and that democracies still exercising the death penalty are more likely to engage in militarised interstate disputes (Stein ). Similarly, support for the death penalty has been associated with higher support for war in Iraq or for the torture of terrorism suspects (Liberman , , ).…”
Section: Ideational Factorsmentioning
confidence: 99%